Change of the organisational and legal form of independent public healthcare centres (SPZOZ) and consequences for financing healthcare entity activities - Tomasz Wołowiec; Tomasz Skica (e-Finanse: Financial Internet Quarterly, 2013)
Local government units (LGU) are nowadays facing the very difficult and complicated task of making reasonable decisions regarding the transforming of SPZOZs into capital companies. First, it seems necessary to carry out a simulation of costs and advantages of the assumed models and solutions together with an analysis of advantages and disadvantages of the new legal and organisational forms. The aim of this paper is to assess whether the process of transforming SPZOZs into capital companies is purposeful and reasonable, and to define a way to prepare hospitals for functioning in an altered legislative environment. The paper draws attention to the fact that transformation itself does not guarantee that the results achieved by the given entity will automatically improve. The transformation can bring financial advantages for the newly created company and the local government, from the subsidies and remissions in accordance with art. 197 of the act on medical activity. Yet the conditions for getting such help are quite restrictive and not in every situation can financial help from the central budget be counted on. Such aid could help improve the financial standing of a hospital considerably. Also, it must be remembered that a hospital transformed into a capital company acquires the capacity to go bankrupt. If the new entity generates a loss, it may result in the owner having to raise the initial capital in order to avoid filing a bankruptcy petition by the company. In practice, the financial consequences for the local government are the same as in the case of having to cover losses. The difference lies in the continuity of the provided medical services.
Keywords: E6; H4; H5; H7; 330; local government units; SPZOZs; healthcare system; health care financing; structure of medical service providers